ramR mutations affecting fluoroquinolone susceptibility in epidemic multidrug-resistant Salmonella enterica serovar Kentucky ST198 - Baucheron, Sylvie (Frontiers Media S.A., 2013)
A screening for non-target mutations affecting fluoroquinolone susceptibility was conducted in epidemic multidrug-resistant Salmonella enterica serovar Kentucky ST198. Among a panel of representative isolates (n = 27), covering the epidemic, only three showed distinct mutations in ramR resulting in enhanced expression of genes encoding the AcrAB-TolC efflux system and low increase in ciprofloxacin MIC. No mutations were detected in other regulatory regions of this efflux system. Ciprofloxacin resistance in serovar Kentucky ST198 is thus currently mainly due to multiple target gene mutations.